Patient satisfaction with nutrition services amongst cancer patients treated with autologous stem cell transplantation: a comparison of usual and extended care. (28th June 2013) - Hung, Y.‐C.; Bauer, J.; Horsley, P.; Isenring, E.
Abstract: Background: This study aimed to determine patient satisfaction with clinical nutrition services delivered by an accredited practicing dietitian amongst cancer patients treated with autologous stem cell transplantation that was provided with usual and extended care at 100 days post‐transplantation. Methods: Patients were randomised to receive usual nutrition care or extended nutrition care during the course of their stem cell transplantation. After hospital discharge, usual care patients received no further nutrition support, whereas extended care patients received telephone dietary counselling from the same dietitian for up to 100 days post‐transplantation. The patient satisfaction with clinical nutrition service questionnaire was completed anonymously at 100 days post‐transplantation. Group comparisons were made using independent t ‐tests. Results: Thirty‐seven patients consented to participate in the study (54% male; mean age 58.7 ± 9.5 years; median body mass index 26.8 kg m –2, range 16.4–47.6 kg m –2 ); 33 patients completed the study and 28 patients returned the questionnaire (response rate = 85%). All components of the questionnaire were rated highly by both groups; there was no significant difference between the groups ( P  > 0.05). Although not statistically significant, extended care patients who received at least three telephone calls rated a higher overall satisfaction compared to those who received less calls; this difference was clinically important (score difference = 0.56). Conclusions: Cancer patients treated with autologous stem cell transplantation were satisfied with usual and extended nutrition care. Extended care patients who received at least three telephone calls after hospital discharge were more satisfied than those with less frequent intervention. Further exploration regarding the frequency and intensity of nutrition service is required.